Photoprotection mechanism in the 'Fuji' apple peel at different levels of photooxidative sunburn. Issue 1 (21st October 2014) - Zhang, Jiangli; Niu, Junping; Duan, Ying; Zhang, Mengxia; Liu, Jingying; Li, Pengmin; Ma, Fengwang
<x xml:space="preserve">Abstract</x> The xanthophyll cycle, flavonoid metabolism, the antioxidant system and the production of active oxygen species were analyzed in the peel of 'Fuji' apples re‐exposed to sunlight after extended periods of fruit bagging treatment, resulting in different levels of photooxidative sunburn. After re‐exposing bagged fruits to sunlight, the production of active oxygen species and the photoprotective capacity in apple peels were both significantly enhanced. As sunburn severity increased, the concentration of hydrogen peroxide increased, while xanthophyll cycle pool size decreased. For the key genes involved in flavonoid synthesis, expressions of MdMYB10 and MdPAL were upregulated, whereas the expressions of MdCHS, MdANS, MdFLS and MdUFGT were downregulated in sunburnt fruit peel. Correspondingly, concentrations of both quercetin‐3‐glycoside and cyanidin‐3‐galactoside decreased. Total ascorbate concentrations decreased as sunburn severity increased, with the decrease being faster for oxidized than for reduced ascorbate. Transcription levels of MdGMP, MdGME, MdGGP, MdGPP, MdGalDH and MdGalLDH, the genes involved in ascorbate synthesis, were similar in non‐sunburnt and sunburnt fruit peels, whereas activities of l‐galactose dehydrogenase and l‐galactono‐1, 4‐lactone dehydrogenase decreased in severely sunburnt peel. Although activities of superoxide dismutase and ascorbate peroxidase increased, the activities of monodehydroascorbate reductase, dehydroascorbate reductase and glutathione reductase decreased as sunburn severity increased. In summary, the occurrence of photooxidative sunburn in 'Fuji' apple peel is closely associated with a relatively lower xanthophyll cycle pool size, reduced levels of ascorbate reduction and synthesis and reduced flavonoid synthesis. Our data are consistent with the idea that ascorbate plays a key role in protecting apple fruit from photooxidative sunburn.